Mary Poppins - Stevenson, Robert, 1905-1986; Walsh, Bill, 1913-1975; DaGradi, Don; Colman, Edward, 1905-1995; Warburton, Cotton, 1911-1982; Sherman, Richard M., 1928-; Sherman, Bob, 1940-2004; Andrews, Julie; Van Dyke, Dick; Tomlinson, David, 1917-2000; Johns, Glynis; Dotrice, Karen; et al. (California Buena Vista Home Entertainment, 2013)
A beloved classic shines like never before with an all-new digital restoration. Winner of five Academy Awards, including best actress (Julie Andrews), best song (Chim Chim Cher-ee), and best visual effects. Mary Poppins flies out of the windy London skies and into the home of two mischievous children. With the help of a carefree chimney sweep named Bert (Dick Van Dyke), the spirited nanny turns every chore into a game, and every day into a 'Jolly Holiday.'
Title from container.
Originally produced as a motion picture in 1964.
Based on the book by P.L. Travers.
Director of photography, Edward Colman ; editor, Cotton Warburton ; music, Richard M. Sherman, Robert B. Sherman.
Julie Andrews, Dick Van Dyke, Ed Wynn, Hermione Baddeley, Karen Dotrice, Elisa Lanchester, Glynis Johns, David Tomlinson, Matthew Garber.
MPAA rating: G.
Keywords: Poppins, Mary (Fictitious character) -- Drama; Nannies -- England -- London -- Drama; Father and child -- England -- London -- Drama; Friendship -- England -- London -- Drama; Musical films; Fiction films; Feature films; Film adaptations; Video recordings for the hearing impaired